PERANAN PLASMAFERESIS PADA KELAINAN NEUROLOGI - Meiti Frida, Hendra Permana (NEURONA, 2013)
OF NEUROIMMUNOLOGICAL DISEASESARE SUBJECTS THAT REQUIRE FURTHER UNDERSTANDING MAINLY FROM THE PATHOPHYSIOLOGY AND MANAGEMENT ASPECTS THESE ARE VERY RARE CASES BUT THEY TEND TO INCREASE THE DISABILITIES AND RESULT IN EMERGENCY CONDITIONS IN NEUROLOGY VARIOUS STRATEGIES HAVE BEEN DEVELOPED FOR MANAGEMENT BASED ON THE CONCEPTS OF AUTOIMMUNITY AND THE MECHANISMS OF NEUROMUSCULAR TRANSMISSION SO THE CHANCE FOR BETTER PROGNOSIS CAN BE ACHIEVED